History of Los Alamos Participation in Active Experiments in Space - Pongratz, Morris B. (Frontiers in Physics, 2018)
Beginning with the Teak nuclear test in 1958, Los Alamos has a long history of participation in active experiments in space. The last pertinent nuclear tests were the five explosions as part of the Dominic series in 1962. The Partial Test Ban Treaty signed in August 1963 prohibited all test detonations of nuclear weapons except for those conducted underground. Beginning with the “Apple” thermite barium release in June 1968 Los Alamos has participated in nearly 100 non-nuclear experiments in space, the last being the NASA-sponsored “AA-2” strontium and europium doped barium thermite releases in the Arecibo beam in July of 1992. The rationale for these experiments ranged from studying basic plasma processes such as gradient- driven structuring and velocity-space instabilities to illuminating the convection of plasmas in the ionosphere and polar cap to ionospheric depletion experiments to the B.E.A.R. 1-MeV neutral particle beam test in 1989. This report reviews the objectives, techniques and diagnostics of Los Alamos participation in active experiments in space.